Migration, poverty, and violence in Mexico: the role of casas de migrantes - Olayo-Mendez, J (2018)
Throughout the past three decades, poverty, violence, and assistance/care have emerged as three interrelated and self-reinforcing dynamics in the migration process in Mexico. However, the study of migration in Mexico has mostly focused on migrants’ journeys or structural dynamics such as violence, neglecting a more systematic analysis of the relationships between migrants, humanitarian actors, contexts, and effects generated by their interactions. The role of poverty in migration processes and how humanitarian organizations function as migration intermediaries also remain underexplored in migration studies. This study contributes toward filling this gap on the bases of an interdisciplinary theoretical framework and qualitative research conducted along migration routes in Mexico. The project explores different dynamics in the migration process by analysing the interactions between migrants and casas de migrantes (migrant shelters) in Mexico. It incorporates semi-structured interviews that include a multidimensional poverty measurement; in-depth interviews with migrants, humanitarian organizations, and other actors; and participant observations. Methodologically, casas de migrantes are an object of inquiry, the place where the interactions with migrants occur, and the space where the dynamics of poverty, violence, and assistance/care converge. This study demonstrates how poor migrants use casas de migrantes as one of several resources to cope with hardship and precariousness during their journeys. At the same time, the study reveals how violence plays a significant role in migrants’ journeys, leading them to seek safety in shelters. Thus, the main contributions of this research are the conceptualization of casas de migrantes as a type of humanitarianism that I call ‘humanitarianism from below’, and an understanding of the significant role the casas de migrantes play as migration intermediaries, which makes them part of the humanitarian governance architecture of migration in Mexico.